Sistem Informasi Penerimaan Peserta Didik Baru Berbasis Website dengan Menggunakan Metode Agile - Robby Sallam; Eko Setia Budi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Education is to develop the potential that humans have because human existence cannot be separated from the environment. One of the institutions for developing human potential is school. School is a center of learning and as a process of socialization and cultivation of abilities, values, attitudes, character and behavior can only occur with the conditions of infrastructure, educational staff, curriculum system and community environment. PPDB at PGRI GANDOANG SMP still uses manual methods which indicate that forms are lost, damaged, reports are time-consuming as well. There is an error in PPDB biodata when inputting manually. And also reporting to the Principal regarding PPDB is less effective and efficient. To solve existing problems. For this reason, a website-based PPDB information system was created with a limited time using an agile method, this method uses a short development cycle, or what is also called a "sprint" to focus on continuous improvement in the development of a product or service. In its development, there are 7 types of agile modeling models, including crystal, dynamic system development methodology, adaptive software development, feature driven development, extreme programming (XP), and SCRUM.Therefore, a new student registration information system is needed that improves human resources. The results that will be achieved are PPDB information that is easily accessible anywhere, committee reporting is more efficient, accurate, does not take time, errors or errors in PPDB biodata occur, so an appropriate method is needed to maximize the registration information system.